INDUCTION OF GENETIC VARIABILITY AND ISOLATION OF MUTANTS IN DOUBLE TYPE TUBEROSE (Polianthes tuberosa L.) VAR. SUVASINI - RANJAN SRIVASTAVA; POOJA KAINTHURA; SATISH CHAND; HEEBA BELWAL AND KRITIKA PANT (The Bioscan, 2021)
The investigation was carried out to study the effect of various mutagenic treatments on vegetative and floral characters on different cultivars of tuberose and isolation of promising mutants. Four varieties viz., Kalyani Single, Kalyani Double, Suvasini and Prajwal were treated with 2 doses each of gamma rays viz., (0.5 Kr, 1.5 Kr), X-rays (0.6 Kr, 1.2 Kr) and Ethyl Methyl Sulphonate (0.1 per cent, 0.2 per cent). The plant height ranged from 18.64 cm to 29.52 cm, spike length ranged from 54.38 cm to 89.21 cm and total florets per spike ranged from 13.50 to 42.57 among different treatment combinations. Six mutants were obtained exhibiting dwarfness in plant height (18.64 cm) [cv. Prajwal treated with EMS (0.2%)], increase in number of petals per floret (8) (cv. Prajwal treated with 1.2 Kr X-rays), fusion of two floret into one [cv. Suvasini and cv. Prajwal treated with EMS (0.2%)], decrease in number of whorl per floret (2) [cv. Suvasini with 1.2 Kr gamma rays treatment] and presence of stamen in double type cultivar (cv. Suvasini with plant treated with 1.2 Kr X-rays).